Thrust Faults Promoted Hydrocarbon Leakage at the Compressional Zone of Fine-Grained Mass-Transport Deposits - Sun, Qiliang; Xie, Xinong; Wu, Shiguo; Yin, Guorui (Frontiers in Earth Science, 2021)
Fine-grained mass-transport deposits (MTDs), especially their compressional toe zones, are traditionally considered as effective seal to constrain the underneath vertical fluid migration. However, this study documents thrust faults at the compressional toe zone of fine-grained MTDs that could disaggregate the seal competence and promote vertical fluid flow. The investigated referred to as MTD-a, lies directly over a large hydrocarbon reservoir that is located within the Central Canyon of northern South China Sea, which is examined by using high-resolution 3D seismic and borehole data. Thrust faults and irregular blocks composed of coarse-grained sandstones are observed in the compressional zone of the MTD-a’s toe. More importantly, seismic evidence (e.g., enhanced seismic reflections) suggests that a large amount of hydrocarbons from the underlying reservoir penetrated through the MTD-a along these thrust faults, and charged into the coarse-grained sandstone blocks. This clear evidence that of thrust faults compromising the MTD’s seal effectiveness and thus facilitating the vertical fluid flow through the non-permeable strata demonstrate the importance of re-assessing the seal capacity of MTD.